Entrepreneurial orientation, resources and capabilities: A conceptual framework review for innovation [Orientación emprendedora, recursos y capacidades: Una revisión de su marco conceptual para la innovación] (2017)
The entrepreneurial orientation allows to develop innovative organizational activities and is considered as a source of business renewal in turbulent environments. The purpose of this article is to relate the entrepreneurial orientation with other management disciplines according with the call of seminal authors to strengthen the theoretical field. This study reviews the recent literature in scientific databases like Scopus. The main results shows the different conceptual frameworks that widely relate dynamic capabilities and resource base view as theoretical fields which incorporate new analysis elements that allow the development of innovation capabilities. © 2017.